Genome-Wide DNA Methylation Modified by Soy Phytoestrogens: Role for Epigenetic Therapeutics in Prostate Cancer? - KARSLI, SEHER (MARY ANN LIEBERT, INC, 2015)
In prostate cancer, DNA methylation is significantly associated with tumor initiation, progression, and metastasis. Previous studies have suggested that soy phytoestrogens might regulate DNA methylation at individual candidate gene loci and that they play a crucial role as potential therapeutic agents for prostate cancer. The purpose of our study was to examine the modulation effects of phytoestrogens on a genome-wide scale in regards to DNA methylation in prostate cancer. Prostate cancer cell lines DU-145 and LNCaP were treated with 40 mu M of genistein and 110 mu M of daidzein. DNMT inhibitor 5-azacytidine (2 mu M) and the methylating agent budesonide (2 mu M) were used to compare their demethylation/methylation effects with phytoestrogens. The regulatory effects of phytoestrogens on DNA methylation were analyzed by using a methyl-DNA immunoprecipitation method coupled with Human DNA Methylation Microarrays (MeDIP-chip). We observed that the methylation profiles of 58 genes were altered by genistein and daidzein treatments in DU-145 and LNCaP prostate cancer cells. In addition, the methylation frequencies of the MAD1L1, TRAF7, KDM4B, and hTERT genes were remarkably modified by genistein treatment. Our results suggest that the modulation effects of phytoestrogens on DNA methylation essentially lead to inhibition of cell growth and induction of apoptosis. Genome-wide methylation profiling reported here suggests that epigenetic regulation mechanisms and, by extension, epigenetics-driven novel therapeutic candidates warrant further consideration in future omics studies of prostate cancer.
Keywords: FACTOR-KAPPA-B; CELL-LINES; TELOMERASE ACTIVITY; ANDROGEN RECEPTOR; BREAST-CANCER; MICROARRAY ANALYSIS; SEQUENCING REVEALS; CATALYTIC SUBUNIT; MITOTIC ARREST; GENISTEIN